2023
DOI: 10.3390/cancers15092605
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CA125 Significantly Improves Risk Stratification in High-Grade Endometrial Cancer

Abstract: Patients with high-grade endometrial carcinoma (EC) have an increased risk of tumor spread and lymph node metastasis (LNM). Preoperative imaging and CA125 can be used in work-up. As data on cancer antigen 125 (CA125) in high-grade EC are limited, we aimed to study primarily the predictive value of CA125, and secondarily the contributive value of computed tomography (CT) for advanced stage and LNM. Patients with high-grade EC (n = 333) and available preoperative CA125 were included retrospectively. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The usefulness of small-molecule markers for EC diagnosis is worthy of exploration. Human epididymal protein 4 (HE4), carbohydrate antigen 125 (CA125) and carbohydrate antigen 199 (CA199) are widely used in the diagnosis of gynecological tumors ( 12 - 14 ). Despite this, the prognosis of EC has not been significantly improved ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of small-molecule markers for EC diagnosis is worthy of exploration. Human epididymal protein 4 (HE4), carbohydrate antigen 125 (CA125) and carbohydrate antigen 199 (CA199) are widely used in the diagnosis of gynecological tumors ( 12 - 14 ). Despite this, the prognosis of EC has not been significantly improved ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this field, attempts to identify biomarkers of lymph node invasion are continuously produced, which have led, for example, to recently highlighting the role played by CD47 in the progression of colorectal cancer [22]. In the case of highgrade endometrial cancer, Lombaers et al reported that the increased risk of lymph node metastasis observed in patients with stage III-IV disease was associated with elevated levels of cancer antigen 125 (CA125) and reduced overall survival, confirming its predictive value [23]. In patients with lung adenocarcinoma, Yu and colleagues revealed that the expression of one member of the mitogen-activated protein kinase family, MAPK15, was positively correlated with lymph node metastasis.…”
mentioning
confidence: 99%